THE USE OF CIRC TO IMPROVE STUDENT’S READING ABILITY - Adri, Adriana; Haryudin, Acep (IKIP Siliwangi, 2019)
The purpose of research was to find whether the learning model of the CIRC based on student learning was effective in improving reading ability in English learner. This activity aims to get experience in learning process and education activities that is used as a provision to become a candidate for educator. Researcher need to be able to have values, attitudes, knowledge and the skills needed as an english teacher. Research activities starts from observation to implementation in learning process in class and activity carried out after doing consultation with the teacher supervisor first and also guidance with the Lecturer Field Advisor. In teaching process the writer found in class that students need to improve their reading ability. That's why the writer use the titte in this journal is The Use Of Circ To Improve Student's Reading Ability. CIRC is Cooperative Integrated Reading and Composition. Implementation of this research was carried out in the class XI Manajemen Pemasaran SMK YPKKP Bandung.